Association of variations in the CAT and prognosis in lung cancer patients with platinum-based chemotherapy - Liu, Jia-Si; Liu, Jun-Yan; Xiao, Qi; Li, Xiang-Ping; Chen, Juan; Liu, Zhao-Qian (Frontiers in Pharmacology, 2023)
Abstract Purpose: To explore the relationship between ATM, ATR and CAT polymorphisms and prognosis of lung cancer patients received platinum-based chemotherapy. Methods: 404 patients with lung cancer who received platinum-chemotherapy were enrolled and DNA typing was performed. Cox regression analysis and stratification analyses was performed to assess relationships between OS and PFS with SNPs genotypes. The prognosis of lung adenocarcinomaand squamous cell carcinomapatients was analyzed with The Cancer Genome Atlas (TCGA) database according to the grouping of CAT expression. Results: CAT rs769217 was significantly related to PFS of patients with lung cancer who received platinum-chemotherapy. In the Additive model, rs769217 was associated with PFS (HR=0.023, 95% CI = 0.581-0.960, P = 0.023). In the Dominant model, CT and TT genotypes led to lung cancer progression 0.747 times more than CC genotype. In stratification analyses of association between CAT rs769217 polymorphisms and PFS, the HR of patients at stage IV in additive model was 0.73, and HR was 0.745 (P = 0.034) in dominant model. For OS analyses, HR was 0.672 in the older lung cancer patients (> 55 years old) in additive model. Meanwhile, in the Dominant model, it was found that the older patients with CT and TT genotypes had better prognosis, and the risk of death after receiving platinum-based chemotherapy was 0.692 times that of patients with CC genotype (P = 0.037). TCGA data shows that LUAD patients with high CAT expression have longer OS (P=0.020). Conclusion: CAT rs769217 is significantly related to PSF of platinum-based chemotherapy in lung cancer patients and may be a biomarker for predicting the prognosis of lung cancer patients with platinum-based chemotherapy.